Cumulative live birth rates following insemination with donor spermatozoa in single women, same-sex couples and heterosexual patients. Issue 6 (December 2020) - Linara-Demakakou, Elena; Bodri, Daniel; Wang, Jinjun; Arian-Schad, Mimi; Macklon, Nick; Ahuja, Kamal
Abstract: Research question: What is the cumulative live birth rate (LBR) following donor intrauterine insemination (IUI-D) treatment in a large, retrospective, single-centre cohort of single women, same-sex couples and heterosexual patients? Design: Outcomes from 8922 treatments performed in 3333 consecutive women (45% single, 43% from same-sex and 12% from heterosexual couples) were analysed in a 13-year retrospective study from a private, HFEA-regulated UK centre between January 2004 and December 2016. Results: A total of 795 live births resulted in an overall delivery rate of 8.9% per cycle, including 24 (3%) twins. Age-specific crude and expected cumulative LBR calculated in four age groups (<35, 35–37, 38–39 and 40–42 years) were 29, 23, 21, 12% and 66, 49, 54, 28%, respectively. A plateau was reached after six cycles, beyond which there were few additional live births. There was no significant difference in cumulative LBR between single women and same-sex couples. In a multivariate analysis, female age (adjusted odds ratio [aOR] 0.92; 95% confidence interval [CI] 0.90–0.93; P < 0.0001), previous live birth following IUI-D (aOR 2.15; 95% CI 1.69–2.73; P < 0.0001) and mild stimulation (aOR 1.27; 95% CI 1.09–1.48; P = 0.02) had a significant effect on outcome, but relationship status or cycle rank did not. Conclusions: These results indicate there is little benefit performing more than six cycles of IUI-D in all women up to 40 years old, including those from same-sex relationships, while only three attempts seem reasonable in those aged 40–42 years. These results do not reflect current clinical guidelines in the UK. The authors found that consecutive IUI cycles, especially with mild stimulation, were an efficient treatment in all indications.